The impact of agricultural extension services in the context of a heavily subsidized input system: The case of Malawi - Ragasa, Catherine; Mazunda, John; Kadzamira, Mariam (International Food Policy Research Institute, 2016)
This paper aims to test this hypothesis and to contribute to better understanding of strategies to revitalize the agricultural extension system in Malawi. Specifically, it examines the interplay between the fertilizer subsidy and access to extension services, and their impact on farm productivity and food security in Malawi. Results show that the fertilizer subsidy has inconsistent impact on farm productivity and food security; at the same time, access to agricultural advice was consistently insignificant in explaining farm productivity and food security. Further analysis, however, shows that when access to extension services is unpacked to include indicators of usefulness and farmers’ satisfaction, these indicators were statistically significant. Households who reported that they received very useful agricultural advice had greater productivity and greater food security than those who reported receiving advice that they considered not useful. This result implies the need to ensure the provision of relevant and useful agricultural advice to increase the likelihood of achieving agricultural development outcomes